Health and disease in two villages in South-Eastern Lesotho : a social anthropological perspective - Heap, Marion (Social Anthropology, 2023)
Macro morbidity and mortality data identify major disease and health trends for large populations. It is also well known that high infant mortality rates, high incidence of infectious fevers, as well as the variety of diseases commonly associated with malnutrition, are correlated with social conditions of poverty. However, these broad trends say little about peoples' experiences of health and disease in conditions of poverty at the grass roots level. This thesis addresses this issue by focusing on how people maintain health and cope with disease in two villages in south-eastern Lesotho. It is primarily a descriptive study of the social dimensions of health and disease-coping strategies in a situation of underdevelopment, where the essential resources pertaining to health, viz food, income, shelter, clean water, and sanitation are inadequate, largely as a result of the historical and on-going political and economic processes beyond the control of the local people. The thesis illustrates that in response to poverty, scarce resources are redistributed via a number of social relationships, in order to provide health for a wide range --of individuals. Thus, there is no clear correlation between material differentiation of households and bett.er access to health. Material differentiation does play some role in recognition of disease and choice of therapy~ This is best illustrated by the fact that extreme poverty limits the ·individual's choice of therapy, and frequently prevents them from adopting the sick role. In contradiction to earlier notions that the 'system of explanation' is the primary factor which determines the individual's utilisation of 'Western' or 'traditional' medical systems, there are numerous other factors which play a role in recognition of disease and choice of therapy, such as cost and availability in a geographic area. Moreover, against a quantitative baseline of the villagers' perceptions of their disease experience, incidences of invocation of the supernatural (such as 'witchcraft') are rare. This suggests that medical anthropology's interest in incidences of supernatural explanation have tended to underplay the extent to which people are able to comprehend and utilise natural explanation. The focus of this study - the relationships between health and disease and natural and supernatural explanation - moves away from the singular disease emphasis of medical anthropology. It is suggested that by viewing disease as 'conflict', many of the problems associated with this approach can be overcome and the interrelationship. Between health and disease re-established.